The Effect of "Read-Ask-Paraphrase"- RAP Strategy on ‎Improving the Reading Comprehension Skills among ‎Students with Learning Disabilities in Jordan - Muhaidat ‎, Mohammad; Al-Smadi, Amal (Jordan Journal of Educational Sciences, 2021)
The present study aimed to investigate the impact of the use of the "paraphrasing " strategy (RAP) to improve reading comprehension at the literal and deductive levels of a sample of students with learning disabilities. The study sample consisted of (60) students from fifth-and sixth-grade students who were chosen intentionally from four schools in Irbid Governorate. A training program based on the Paraphrasing strategy (RAP) was prepared, in addition to preparing a reading test for the purpose of selecting the study members, as well as preparing a reading comprehension test. The study members were randomly distributed equally to two groups: experimental and control and pre-test was applied to the two groups. The experimental group was exposed to the training program, while the control group was subjected to training in the traditional way and post-test was applied to both groups. The results indicated that there are statistically significant differences between the mean scores of students in the two groups, in the total reading comprehension test and its levels, in favor of the experimental group. There are no statistically significant differences between the mean scores of students in the total reading comprehension test and its levels according to the gender variable in the post-measurement and the results indicated that there are no statistically significant differences between the mean scores of students in the post-test and the follow-up test in the total reading comprehension test and its levels In other words, the positive impact of the training program continued after two weeks of applying the post-test